Facets of heat shock protein 70 show immunotherapeutic potential - Todryk, Stephen M (Blackwell Science Inc, 2003)
Amongst the families of intracellular molecules that chaperone and assist with the trafficking of other proteins, notably during conditions of cellular stress, heat shock protein (hsp) 70 is one of the most studied. Although its name suggests that expression is exclusively induced during cellular hyperthermia, members of the hsp70 family of proteins can be constitutively expressed and/or induced by a range of other cellular insults. The ubiquitous presence of hsp70 in eukaryotic and prokaryotic cells, combined with its high degree of sequence homology and intrinsic immunogenicity, have prompted the suggestion that inappropriate immune reactivity to hsp70 might lead to pro-inflammatory responses and the development of autoimmune disease. Indeed, hsp70 has been shown to be a potent activator of innate immunity and aberrant expression of hsp70 in certain organs promotes immunopathology. However, studies also suggest that hsp70 might have immunotherapeutic potential, as hsp70 purified from malignant and virally infected cells can transfer and deliver antigenic peptides to antigen-presenting cells to elicit peptide-specific immunity and, in contrast to its reported pro-inflammatory effects, the administration of recombinant hsp70 can attenuate experimental autoimmune disease. This review focuses on the immunoregulatory capacity of hsp70 and its potential therapeutic value.